Collective Online Learning Practice in Higher Education in Biak, Indonesia: Navigating Digital Disparity - Dewi Zulaiha; Pegiawan Basopi (Presscience, 2026)
Digital disparity significantly challenges online learning implementation in remote area in Indonesia, particularly in Papuan context. This study explores the unique online learning model adopted by English Education (PBI) students in private university in Biak, Papua as a resilient response to infrastructure limitations. Using a qualitative case study approach, data were gathered through semi-structured interviews and field observations. The study involved 25 students, along with key stakeholders and lecturers, to provide a comprehensive perspective on the local educational ecosystem. The results reveal that students navigate digital gaps through